2019
DOI: 10.4103/ajns.ajns_259_19
|View full text |Cite
|
Sign up to set email alerts
|

Medullary hemorrhage caused by foramen magnum dural arteriovenous fistula successfully obliterated using combination of endovascular and surgical treatments: A case report and literature review

Abstract: The authors describe an extremely rare case of foramen magnum dural arteriovenous fistula (DAVF), Cognard type V, presented with medullary hemorrhage caused by venous varix on the lateral medullary draining vein embedded into the medulla oblongata. Following mild myelopathy for 3 days, a 20-year-old male developed dyspnea, generalized seizures, loss of consciousness, and finally cardiac arrest. After successful resuscitation, computed tomography scan (CT) of the brain was obtained and showed acute medullary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…1 30 At the same time, most patients with Spinal dural arteriovenous stula after surgical intervention did not have serious complications. 5 cases of them had sensory dysfunction or numbness, 1 28 30 37 38 6 cases of them had decreased strength or even gait instability, 30-32, 37, 38 1 cases had hemiplegia 31 and 1 case had quadriplegia, 33 However, the mild complications of the cases recovered quickly, only 3 more serious cases received rehabilitation treatment. 31,35,37 At present, the effect of extracorporeal shock waves on spasticity caused by central diseases is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 30 At the same time, most patients with Spinal dural arteriovenous stula after surgical intervention did not have serious complications. 5 cases of them had sensory dysfunction or numbness, 1 28 30 37 38 6 cases of them had decreased strength or even gait instability, 30-32, 37, 38 1 cases had hemiplegia 31 and 1 case had quadriplegia, 33 However, the mild complications of the cases recovered quickly, only 3 more serious cases received rehabilitation treatment. 31,35,37 At present, the effect of extracorporeal shock waves on spasticity caused by central diseases is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for SDAVF include endovascular embolization and surgical ligation of the stula [28][29][30][31][32][33][34][35][36][37][38] . Endovascular embolization is less invasive.…”
Section: Discussionmentioning
confidence: 99%
“…Microsurgery has also been useful in cases with symptoms caused by the mass effect of the dilated venous pouch and the shunt fistula (1). Chen et al reported that trigeminal neuralgia due to a foramen magnum DAVF compression was completely relieved after surgical disconnection (9). In addition, although seldom reported, surgery-related complications (intracranial hematoma, intracranial infection, etc.,) cannot be completely avoided.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the past decade, with remarkable advances in the endovascular techniques providing highly flexible hydrophilic-coated catheters and new non-adhesive liquid embolic agents, such as Onyx and N-butyl-cyanoacrylate (NBCA) glue, endovascular embolization of the fistula has become an alternative option for treating the foramen magnum DAVFs (6)(7)(8). It has been reported that ∼80% of the foramen magnum DAVFs in the literature were treated endovascularly (9). Nevertheless, the incomplete obliteration and reoccurrence of the fistula after endovascular embolization could not be underestimated, and some cases even required staged or salvage combined surgeries (1,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation